Impact of exposure to phenols during early pregnancy on birth weight in two Canadian cohort studies subject to measurement errors. (November 2018) - Lester, Fiona; Arbuckle, Tye E.; Peng, Yingwei; McIsaac, Michael A.
Abstract: Background: It is of interest to know whether early pregnancy exposure to phenols such as bisphenol-A (BPA) or triclosan (TCS) negatively impacts birth weight outcomes. Exposure to these chemicals is widespread in the Canadian population but obtaining accurate measurements of average exposure is difficult because these chemicals are rapidly excreted from the body, causing body levels to fluctuate both within and between days, as observed in a recent Canadian study (P4). This measurement error can attenuate the estimated effects of exposures. Methods: Data from two Canadian cohort studies, the Plastics and Personal-care Products use in Pregnancy (P4) Study and the Maternal-Infant Research on Environmental Chemicals (MIREC) Study, such that all participants with complete BPA or TCS exposure and outcome data were used (MIREC n  = 1822, P4 n  = 68). We used regression calibration to correct for the attenuating effects of exposure measurement error when modeling the effect of first trimester BPA or TCS exposure on four birth weight outcomes: birth weight (BW), low birth weight (LBW), small for gestational age (SGA) and large for gestational age (LGA). Specific gravity, time of day, and time since last urine void were also controlled in the analysis. Results: TCS exposure has a marginally significant association with SGA only with odds ratio 0.87 and 95% confidence interval (0.74, 1.00). It also has a marginally significant association with LGA in male offspring with odds ratio 1.11 and 95% confidence interval (1.00, 1.25). The effects of BPA on the four birth outcomes were insignificant. Conclusions: Increased TCS exposure during pregnancy is marginally associated with decreased odds of having SGA offspring. It is possibly associated with decreased BW in males and decreased odds of LBW, though these associations were not present in measurement error corrected models. TCS is possibly associated with increased odds in male offspring of being LGA, though this relationship was not present in models not corrected for measurement error. The study finds no significant effects of BPA on birth weight outcomes, which may be due to more severe measurement error in a single observation of BPA. Highlights: The impact of early pregnancy exposure to phenols on birth weight is still unclear. Assessing the impact is difficult due to measurement errors in exposure measurements. A regression calibration is used to assess the impact with presence of measurement error. A marginal positive association between triclosan and small for gestational age is observed. The effects of bisphenol-A on birth weight outcomes are insignificant.